Pre-Calc-please check

posted by .

Please check this for me
expand (3z-2b)^5 using Binomial Theorem
(a+b)^n = n on top sigma in middle k=0 to right (n/k)a^(n-k)b^k

(3a-2b)^5 = 5 on top sigma in middle k=0 on bottom(5/k)(3a)^5-k(-2b)^k

(5/0)(3a)^5(-2b)^0+(5/1)(3a)^4(-2b)^1 +(5/2)(3a)^3(-2b)^2

+(5/3)(3a)^2(-2b)^3 + (5/4)(3a)^1(-2b)^4+(5/5)(2a)^0(-2b)^5

=243a^5-810a^4b+1080a^3b^2+-720a^2b^3+240ab^4-32b^5

5!/(5-5)!5!=5!/1-5!=5!/5!1

(5/0)=5!/(5-0)!0!=5!/5!0!=1

  • Pre-Calc-please check -

    please delete last two lines-that was just my work I calculated- it shouldn't e there
    actual answer is 243a^5-810a^4b + 1080a^3b^2 -720a^2 b^3 + 240ab^4-32b^5

  • Pre-Calc-please check -

    Don't know if you have to go into sigma notation unless your instructor wants you to do it that way.

    I would have in front of me Pascal's Triangle , where I would need the row
    1 5 10 10 5 1

    so (3a - 2b)^5
    = 1(3a)^5 + 5(3a)^4 (-2b) + 10(3a)^3 (-2b)^2 + 10(3a)^2 (-2b)^3 + 5(3a) (-2b)^4 +1(-2b)^5
    = 243a^5 - 810a^4 b + 1080a^3 b^2 - 720a^2 b^3 + 240a b^4 - 32b^5

    Your answer is correct

  • Pre-Calc-please check -

    Thank you for checking

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    find the indicated sum 4 on top of sigma symbol i=1 on the bottom of sigma symbol 3^i on the right side please help me figure this out
  2. math- Algebra 2

    I have absolutely no idea how to do this please help! Find the sum: it has the sigma sign with 12 at the top, (10k-8)(6k+7) in the middle and k=1 at the bottom
  3. Maths

    Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
  4. Maths

    Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
  5. Maths

    Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
  6. Algebra II

    Please help-I need to write 4+6+8+10 in sigma notation would it be sigma sign in middle (3) on top of sign, n=0 on bottom of signma notation and to the right it would be (4+2n) so it would look like-- (3) (sigma in middle) (4+2n) n=0
  7. Pre-Calc-Please check

    1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) = -1/5*1/4^(10-1) =-1/5*(1/4)^9 …
  8. Pre-Calc-Please check answer

    1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2n+4 to the right of the signma sign 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) …
  9. Pre-Calc-Please check answer

    1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2n+4 to the right of the signma sign 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) …
  10. Pre-CalcPlease check

    Please check: 1.Write in expanded form: this is a sigma notation- 4 on top signma in middle k=1 on bottom to right of sigma is (k-1)(k-2) I solved: k=1 (1-1)(1-2)=0(-1)=0 K=2 (2-1)(2-2) = 1(0)=0 k=3(3-1)(3-2)=2(1)=2 k=4 (4-1)(4-)=3(2)=6 …

More Similar Questions